2021
DOI: 10.1093/bib/bbab206
|View full text |Cite
|
Sign up to set email alerts
|

A predictive paradigm for COVID-19 prognosis based on the longitudinal measure of biomarkers

Abstract: Novel coronavirus disease 2019 (COVID-19) is an emerging, rapidly evolving crisis, and the ability to predict prognosis for individual COVID-19 patient is important for guiding treatment. Laboratory examinations were repeatedly measured during hospitalization for COVID-19 patients, which provide the possibility for the individualized early prediction of prognosis. However, previous studies mainly focused on risk prediction based on laboratory measurements at one time point, ignoring disease progression and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
7
2
Order By: Relevance
“…Consistent with this study, other studies found the trend of CRP 9 , 10 , 18 , LDH 10 , 11 , 13 , 18 , PLT 11 , 13 , lymphocyte 8 , 13 , urea 11 , 13 , and Cr can discriminate COVID-19 outcome. Our results fairly confirm results of Burke et al study 13 using dynamic time warping analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with this study, other studies found the trend of CRP 9 , 10 , 18 , LDH 10 , 11 , 13 , 18 , PLT 11 , 13 , lymphocyte 8 , 13 , urea 11 , 13 , and Cr can discriminate COVID-19 outcome. Our results fairly confirm results of Burke et al study 13 using dynamic time warping analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Monitoring and allocating inpatients during peaks of COVID-19 can be challenging. Studies tried to propose laboratory profile for monitoring a hospitalized patient using longitudinal weekly values 9 , comparing early and late results 10 , historical regression tree 11 , Wilcoxon sum rank test of daily averages trend 8 , Mann–Whitney test of daily results between mortality and survived 12 , and dynamic time wrapping analysis 13 . This study used the parallel pairwise comparison to investigate the trend of lab results among survivors and non-survivors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the trajectory of C-reactive protein concentration during the first week of hospital admission predicts bacterial co-infection and supports antimicrobial decision-making. 27 More sophisticated, a dynamic risk prediction model for COVID-19 outcome that includes 14 biomarkers was built by using a random forest-based machine learning method and a joint modeling technique 28 while the longitudinal analysis of differentially expressed serum proteins detected 40 proteins whose level increases or decreases with disease severity. 29 Finally, machine learning and plasma proteome analyses were combined to detect an early molecular host response that predicts COVID-19 progression according to age, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…More studies using the joint modeling approach may be found in the literature. For instance, Chen et al 14 used a similar strategy for developing a dynamic risk prediction model for COVID-19 prognosis considering longitudinal measures. Lu et al 15 used a joint approach to study the association of oxygen saturation to the fraction of inspired oxygen ratio and time to death of patients diagnosed with COVID-19.…”
Section: Discussionmentioning
confidence: 99%